Spaceborne Bi- and Multistatic SAR: Potential and Challenges - Krieger, Gerhard; Moreira, Alberto (IEE P-RADAR SON NAV, 2006)
Bi- and multistatic synthetic aperture radar (SAR) operates with distinct transmit and receive antennas that are mounted on separate platforms. Such a spatial separation has several operational advantages, which will increase the capability, reliability and flexibility of future SAR missions. Various spaceborne bi- and multistatic SAR configurations are introduced, and their potential for different applications such as frequent monitoring, wide-swath imaging, scene classification, single pass cross-track interferometry and resolution enhancement is compared. Furthermore, some major challenges such as phase and time synchronisation, bi- and multistatic SAR processing, satellite orbit selection and relative position sensing are addressed. © The Institution of Engineering and Technology 2006.
DLR Import::2019-04-02